1976
DOI: 10.1111/j.1559-1816.1976.tb01327.x
|View full text |Cite
|
Sign up to set email alerts
|

The Tyranny of Numbers: Does Group Size Affect Petition Signing?

Abstract: Conformity research proposes that an individual's tendency to conform increases linearly as a function of group size, reaches an early plateau, and remains stable thereafter, An experiment was performed to test the generality of this notion to a common group pressure situation: petition‐signing. Results revealed no meaningful relationships whatever between the percent of subjects who signed and the number of previous signatures (0 through 8), the forcefulness of the solicitor's approach, and subject's sex. A f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…The results of the first experiment only supported the majority effect hypothesis and showed that, irrespective of consensus level, a majority had more influence than a minority (Goldberg, 1954;Kidd, 1958;Mackie, 1987;Reis et al, 1976). The trend analyses offered no support for the consensus hypothesis and therefore this does not support the mathematical models of social influence.…”
Section: Message-congruent Thoughtsmentioning
confidence: 75%
See 2 more Smart Citations
“…The results of the first experiment only supported the majority effect hypothesis and showed that, irrespective of consensus level, a majority had more influence than a minority (Goldberg, 1954;Kidd, 1958;Mackie, 1987;Reis et al, 1976). The trend analyses offered no support for the consensus hypothesis and therefore this does not support the mathematical models of social influence.…”
Section: Message-congruent Thoughtsmentioning
confidence: 75%
“…The first two focus on the nature of the source of influence. Based on several studies, we tested whether a majority would be more influential than a minority irrespective of consensus level (Goldberg, 1954;Kidd, 1958;Mackie, 1987;Reis et al, 1976). It may be the case that the label 'majority' is sufficient to make members of the minority conform to the majority, with the relative size between them not being important.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, Experiment 1 investigated, for the first time, the effect of group consensus as expressed by the consensus adjectives large versus small on majority and minority influence. We tested two hypotheses concerning the effect of group consensus on social influence: (a) that influence is a linear function of increasing consensus size, that is, the linear consensus hypothesis, large majority > small majority > large minority > small minority (Carlston, 1977;Gerard et al, 1968;Nordholm, 1975;Tanford & Penrod, 1984;Wolf & Latané, 1983), and (b) that consensus does not have an impact on influence but majority status does, which we call the majority source hypothesis, that is, large majority = small majority > large minority = small minority (Goldberg, 1954;Kidd, 1958;Mackie, 1987;Martin et al, 2002;Reis et al, 1976).…”
Section: Methodsmentioning
confidence: 99%
“…Some studies revealed a curvilinear relationship between consensus and influence (e.g., Asch, 1951;Kishida, 1956;Rosenberg, 1961), whereas other studies found a linear relationship between consensus level and influence (e.g., Carlston, 1977;Gerard et al, 1968;Lascu, Bearden, & Rose, 1995;Nordholm, 1975). However, another set of studies failed to find a linear relationship (e.g., Goldberg, 1954;Kidd, 1958;Reis, Earing, Kent, & Nezlek, 1976). The inconsistency among these findings has been attributed to the different tasks employed, the different manipulations of source, and the different perceptions of the majority (see Campbell & Fairey, 1989;Insko, Drenan, Solomon, Smith, & Wade, 1983;Wilder, 1977).…”
Section: Relationship Between Group Consensus and Social Influencementioning
confidence: 99%